MORPHOFUNCTIONAL CONDITION OF THE OVARIES AFTER HYSTERECTOMY - A. S. Fateyeva; I. A. Petrov; O. A. Tikhonovskaya; S. V. Logvinov (Бюллетень сибирской медицины)
Estrogen-deficient state evolving after the removal of the uterus and blood disorders and innervation. In the present analytical review of the literature discusses the features of the structure and function of the ovaries in patients undergoing hysterectomy. Presents comparative data on preservation or removal of the fallopian tubes during a hysterectomy.